2011
DOI: 10.1111/j.1365-2109.2011.02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Water parameters affect anaesthesia induced by eugenol in silver catfish, Rhamdia quelen

Abstract: The present study investigated the effects of water pH (5.0, 7.0 and 9.0), hardness (0, 20 and 120 mg CaCO3 L−1) and temperature (15, 23 and 30 °C) on the induction of sedation and anaesthesia, and subsequent recovery, of silver catfish exposed to eugenol. Moreover, the blood gas tensions (PvO2 and PvCO2) and blood pH in silver catfish acclimated to these temperatures were investigated after exposure to eugenol. Water pH, hardness, temperature and fish size affect the efficacy of eugenol in silver catfish, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 49 publications
2
22
0
1
Order By: Relevance
“…This effect was expected, since these compounds have an anesthetic effect in fish (GOMES et al, 2011, SILVA et al, 2015CUNHA, et al, 2017). Eugenol also presented anesthetic activity in crustaceans (PARODI et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was expected, since these compounds have an anesthetic effect in fish (GOMES et al, 2011, SILVA et al, 2015CUNHA, et al, 2017). Eugenol also presented anesthetic activity in crustaceans (PARODI et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all anesthetic substances used in shellfish are synthetic products such as benzocaine, MS-222 and 2-phenoxyethanol, and the minority are plant extractives (GARR et al, 2012). Essential oils (EOs) of Lippia alba and Aloysia triphylla (PARODI et al, 2012), for example, and isolated substances such as eugenol (GOMES et al, 2011;PARODI et al, 2012) and linalool (HELDWEIN et al, 2014) are effective to anesthetize fish and shrimps. Thus, we can assume that EOs may also be effective in mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that eugenol is an efficient inducer of anesthesia for carps (C. carpio) when used at doses lower than 75 mg L -1 and recommended dosage of 37.5 mg L -1 for anesthesia this specie, to avoid drug toxicity (BITTENCOURT et al, 2013). For South American catfish (R. quelen) GOMES et al (2011) indicated a dosage of 40 ml L -1 is sufficient to induce anesthesia and compensate for the effects of size of fish and water quality. In the studies of HONCZARYK and INOUE (2009) was reported that doses of 30 and 60 mg L -1 applied by spraying in gills of arapaima (Arapaima gigas) were effective for the management of this species.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil there are recent reports of using eugenol (2-methoxy-4-(2-propenyl)phenol), the main component of clove oil (70-90% by weight) or just clove oil as an anesthetic for several species like Centropomus undecimalis (BERNARDES JÚNIOR, et al, 2013), Pimelodus britskii (BERTOZI JÚNIOR et al, 2014), Rhamdia quelen (CUNHA et al, 2010;GOMES et al, 2011;BECKER et al, 2012;SUTILI et al, 2014), Oreochromis niloticus (MOREIRA et al, 2010;, Cyprinus carpio (BITTENCOURT et al, 2013), Colossoma macropomum (INOUE et al, 2011), Pseudoplatystoma reticulatum (SANTOS SANCHEZ et al, 2014b), Gymnotus aff. inaequilabiatus (PÁDUA et al, 2012), Brycon hilarri (FABIANI et al, 2013) among others.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration and efficacy required for induction may vary among species, age, size, gender and even among the parameters of water quality (Walsh and Pease 2002, Woody et al 2002, Gomes et al 2011). According to the literature, proper immersion anesthesia may decrease the incidence of adverse effects and lead to a milder recovery (Acerete et al 2004, Zahl et al 2009).…”
Section: Introductionmentioning
confidence: 99%